Association between physical activity and quality of life in haemodialysed and peritoneal dialyzed patients in Hungary - Enikő Király; Gergő József Szőllősi; Zoltán Jenei; István Kárpáti (Renal Failure)
Background Patients with end-stage kidney disease (ESKD) receiving peritoneal dialysis (PD) or haemodyalisis (PD) appear to be less physically active than healthy persons, a situation that could lead to reductions in quality of life. The aim of the present study was to assess and compare physical activity and health-related quality of life in renal patients on HD and PD programs.Methods In May 2020, 130 patients (106 HD and 24 PD) were enrolled in a study of chronic dialysis programs. All participants received a questionnaire containing information on demographics, treatment, and co-morbidities. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ) short form, and quality of life was measured using the Kidney Disease Quality of Life-Short Form 12 (KDQOL-SF-12) questionnaire comprising mental (MCS) and physical components (PCS). Non-parametric statistical tests were executed with 0.05 as the level of significance.Results The physical activity of patients treated in both HD and PD programs could be considered as low, without a statistically significant difference between the two modalities. For the quality of life measures, we found a significant (p = .004) difference regarding Physical Component Summary (PCS) scores, with higher PCS scores in patients treated in the PD programme compared to HD. Furthermore, higher physical activity levels were associated with better quality of life parameters in both groups.Conclusion This study confirms the importance of physical activity among dialysis patients with ESKD, suggesting that greater activity could be associated with a better quality of life.